2023
DOI: 10.3389/fbioe.2023.1103515
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic fields as a promising therapy for glucocorticoid-induced osteoporosis

Abstract: Glucocorticoid-induced osteoporosis (GIOP) is considered the third type of osteoporosis and is accompanied by high morbidity and mortality. Long-term usage of glucocorticoids (GCs) causes worsened bone quality and low bone mass via their effects on bone cells. Currently, there are various clinical pharmacological treatments to regulate bone mass and skeletal health. Pulsed electromagnetic fields (PEMFs) are applied to treat patients suffering from delayed fracture healing and non-unions. PEMFs may be considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 106 publications
(140 reference statements)
1
0
0
Order By: Relevance
“…Similar results were obtained by other authors [62,63]. A recent review showed positive effects of PEMFs in the treatment of osteoporosis in 23 out of 24 studies included in the study.…”
Section: Osteopenia and Osteoporosissupporting
confidence: 90%
“…Similar results were obtained by other authors [62,63]. A recent review showed positive effects of PEMFs in the treatment of osteoporosis in 23 out of 24 studies included in the study.…”
Section: Osteopenia and Osteoporosissupporting
confidence: 90%
“…Osteoporosis fractures and delayed unions are two examples of bone disorders that can be treated with PEMF therapy [10]. By stimulating osteoblastogenesis and influencing calcium storage and mineral metabolism, PEMF increases both bone volume and density [11]. Electromagnetic field applications in rats, human red blood cells, and human hemoglobin cell-free models have shown that these stimuli can increase tissue oxygenation, microcirculation, and angiogenesis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%